(untitled) (Revista Brasileira de História da Educação, 2012)
BASTOS, Maria Helena Camara; FARIA FILHO, Luciano Mendes de (Org.). A Escola Elementar no Século XIX. O Método Monitorial/Mútuo. Passo Fundo: Ediupf, 1999.